Anregurutta H. Abdul Malik Muhammad's Approach to Da'wah Communication to Socio-Religious Change in Belawa Society - Sirajuddin; A Nurkidam; Ramli; Abd. Rahim Arsyad; Muhammad Qadaruddin (Jurnal Dakwah dan Komunikasi, 2024)
This thesis examines the approach to Islamic communication (da'wah) of Anregurutta H. Abdul Malik Muhammad and its impact on the socio-religious changes in the Belawa community. This study aims to understand Anregurutta's communication and da'wah approach, identify the media used for da'wah, and analyze the socio-religious changes that occurred in the Belawa community. This research employs a qualitative method with data collection techniques through in-depth interviews with informants selected using purposive sampling. The data obtained is analyzed thematically to identify relevant patterns and meanings. The results of the study indicate that Anregurutta H. Abdul Malik Muhammad's approach to Islamic communication emphasizes the principles of Sipakainge (mutual reminding/advising), Siammasei (mutual affection), and Ade Tongang (truthful speech), along with a friendly, easily understood, and persuasive communication style. The media used for da'wah include the Darussalam Mosque, the Madrasah Arabiyah Islamiyah (Islamic Arabic School), and Safari Dakwah (itinerant preaching). The impact of this approach is evident in the socio-religious changes in the Belawa community, particularly in terms of the transformation of religious values, shifts in patterns of socio-religious interaction, socio-religious life, and the strengthening of religious practices.   Â